How to Report Record Open‐Circuit Voltages in Lead‐Halide Perovskite Solar Cells. Issue 1 (11th November 2019) - Krückemeier, Lisa; Rau, Uwe; Stolterfoht, Martin; Kirchartz, Thomas
Abstract: Open‐circuit voltages of lead‐halide perovskite solar cells are improving rapidly and are approaching the thermodynamic limit. Since many different perovskite compositions with different bandgap energies are actively being investigated, it is not straightforward to compare the open‐circuit voltages between these devices as long as a consistent method of referencing is missing. For the purpose of comparing open‐circuit voltages and identifying outstanding values, it is imperative to use a unique, generally accepted way of calculating the thermodynamic limit, which is currently not the case. Here a meta‐analysis of methods to determine the bandgap and a radiative limit for open‐circuit voltage is presented. The differences between the methods are analyzed and an easily applicable approach based on the solar cell quantum efficiency as a general reference is proposed. Abstract : Various definitions of band gaps are used in the perovskite solar cell community as a reference to analyze losses in open‐circuit voltage. This essay proposes a band‐gap independent method to reference voltages that is easy to implement and a meta‐analysis of literature data to illustrate the state of the art and development of voltage losses in perovskite solar cells.